Diagnosis and treatment of a rare case of tubercular gingival enlargement - Tanvi Phull; Harmesh Sharma; Sunidhi Gandhi; Divya Jyoti; Ritu Malhotra; Nandita Katha (Wolters Kluwer Medknow Publications, 2024)
Granulomatous inflammation is a distinctive variant of the chronic inflammatory response. The orofacial tissues may be affected by a wide range of granulomatous diseases. The lesions range from infections, immunological, and reactive, to foreign body granulomas. As is common knowledge, tuberculosis (TB) is a chronic infectious disease that can affect any region of the body, including the mouth. It may involve the tongue in the mouth and have quite peculiar features and forms. Therefore, while uncommon, oral lesions are crucial for the early detection and treatment of primary TB. We discuss a possible instance of gingival TB that manifested as an enlarged gingiva. The patient received a test dose of antituberculous therapy for one month. The antituberculous therapy was completed for the following five months after one month of treatment showed progress. This case report for dentists emphasizes how crucial it is to consider TB in the differential diagnosis of various types of gingival enlargements.